Enhancing Dentistry Students’ Knowledge of Dental Jurisprudence and Ethics through Outcome-Based Instructional Materials as an Instructional Strategy - Eduard M. Riparip (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Dental Jurisprudence and Ethics (DJE), a board-exam subject in the Dentist Licensure Examination, presents challenges for dentistry students due to its complexity and the limited availability of outcome-based instructional materials (OBIM). This study developed and validated an OBIM in DJE using a pretest-posttest experimental design. Two validated instruments were utilized: the OBIM and a 100-item Board-Exam-Patterned Test (BEPT). A total of 276 dentistry students from Centro Escolar University Manila and Makati were assigned to experimental and control groups. Baseline results showed both groups were comparable and demonstrated low knowledge of dental jurisprudence and ethics. Following the intervention, the experimental group achieved significantly higher BEPT posttest scores than the control group. The learning gains remained significant after controlling for baseline differences and reflected a substantial educational effect. The findings demonstrate that the developed OBIM effectively enhances students’ legal knowledge, ethical understanding, and professional preparedness, supporting its institutional adoption in dental education.